Outcomes of deviation from treatment guidelines in status epilepticus: A systematic review. (May 2018) - Uppal, Preena; Cardamone, Michael; Lawson, John A.
Highlights: There is a gap between guidelines on status epilepticus and its management. The proportion of variations ranged from 10.7% to 66%. The most common variation was excessive benzodiazepine use. 5.79 times higher odds of respiratory depression with excessive benzodiazepine use. Abstract: Objective: Due to a gap between published clinical guidelines on status epilepticus SE and clinician management of SE, a systematic review was performed to investigate treatment adherence to SE guidelines and its impact on patient outcomes. Methods: Medline and Embase searches were conducted for studies appraising adherence to SE guidelines (from 1970 and 1st April 2018). The quality of eligible studies was assessed by QUADAS- 2 criteria. Comparison was made between patients where guidelines were followed and not followed. Various patient outcomes including intubation, ICU admission, morbidity and mortality were compared. A Forest plot was used to investigate the effect of adherence on outcome. Results: A total of 3424 titles and abstracts were screened from the initial search after removal of duplicates. A total of 441 full text articles were reviewed in detail, and 22 articles were included in this study. The proportion of deviations ranged from 10.7% to 66.1%. Four studies were descriptive. Eighteen studies looked at the adverse effects of non-adherence. Eight studies showed respiratory depression and intubation were associated with excessive benzodiazepine use. A subset analysis showed 5.79 times higher odds of respiratory depression and intubation], if excessive benzodiazepines were given. The next most common variations were delayed management and insufficient treatment. These variations from the guidelines were associated with prolonged seizures. Conclusions: This review provides preliminary evidence that non-adherence to SE guidelines negatively impacts on patient outcomes. Appropriate and timely treatment is imperative for rapid seizure termination and improving outcomes.